Justice, Peace and Care for Creation: What is at stake? Some South African perspectives - Conradie, Ernst M. (International review of mission, 2010)
This article explores the relationship between the three aspects of the social agenda of the ecumenical movement captured in the motto of “Justice, peace and care for creation”. It investigates the moral, spiritual and theological issues that are at stake from a South African perspective, drawing especially on a recent document entitled “Climate Change – A challenge to the churches in South Africa” (2009), published and endorsed by the South African Council of Churches. It examines the underlying tensions between these concepts and the ways in which one is sometimes prioritized over the other. It concludes that the themes of justice, peace and sustainability may be associated with different aspects of God's work on earth and that this can only be dealt with on the basis of a deeper theological assessment of the whole of God's work.